User grouping-based multiple access scheme for IoT network - Minh-Sang Van Nguyen; Tu-Trinh Nguyen; Dinh-Thuan Do (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
The internet of things (IoT) in 5G and beyond wireless systems is interesting topic since IoT network will be platform to develop applications in the future. IoT will open a door for smart services and new wireless architecture. In this study, we consider multiple access technique applied in two-way cooperative scheme, namely two-way non-orthogonal multiple access (TW-NOMA). We derive expressions of outage probability for considered system using amplify-and-forward (AF) relay protocol, and we show that fixed power allocation factors and target rates are main impacts on performance of AF TW-NOMA. We finally extend many scenarios to evaluate performance of two-user model and outage probability in a two-user scenario are numerically verified. It is confirmed that simulation results show that AF TW-NOMA provides better data rates and user fairness.